PENGARUH VIRTUAL COUPLE EDUCATION TERKAIT PENGETAHUAN TANDA BAHAYA KEHAMILAN DAN PERSALINAN TERHADAP KESIAPAN MENGHADAPI PERSALINAN PADA IBU TRIMESTER III DI PUSKESMAS CIRIMEKAR - Fitri Wulan Sari, (2023)
Pregnancy Danger Signs are symptoms that indicate there is a danger that can occur during pregnancy or childbirth and can result in maternal death if not reported or detected while Labor Preparedness is a program to plan birth readiness and to handle emergencies so that safety in childbirth and preparedness for pregnant women to help get health services and professional care during childbirth. The purpose of this study was to determine the effect of virtual couple education regarding the signs and dangers of pregnancy and childbirth on readiness for childbirth in third trimester mothers. Respondents involved were 34 people who would be given the intervention. This intervention is carried out for 7 days where on the first day an intervention will be given regarding danger signs of pregnancy and on the 4th day an intervention will be given related to readiness for childbirth. This study used a Quasi-Experimental research design with a One-Group Pretest-Posttest Design with Accidental sampling technique. Based on statistical tests using the Mc Nemar test, the results obtained were p-Value = 0.000 so that there was a significant influence on educational knowledge regarding danger signs of pregnancy and childbirth in third trimester pregnant women at the Cibinong Health Center. By providing interventions related to danger signs and readiness for childbirth to minimize these risks.